Kajian Penanganan Wildlife Hazard Guna Meningkatkan Keselamatan di Sisi Udara Bandar Udara Sultan Thaha Jambi - Eldy Dhafina Frahmandar Aqmar; Agoes Soebagio; Lina Rosmayanti (Jurnal Flight Attendant, 2025)
Sultan Thaha Jambi Airport is located close to the city center, only two kilometers away, but there are still many forests around it. Due to its strategic but also vulnerable location, it is very common for wild animals to enter the airport area. The purpose of this study was to identify the causal factors and to find out how to handle wild animals at Sultan Thaha Airport. To overcome this problem, a Safety Risk & Quality Control Unit was formed whose task is to ensure the safety and quality of flights at this airport. This study was conducted by direct observation in the field, and collecting data from related documents. The results of this study concluded that the factors causing wildlife hazards at Sultan Thaha Jambi Airport come from internal conditions, such as infiltration ponds, tall grass, bushes, and trees that are habitats for wild animals. External factors include the existence of residential areas, rice fields, garbage dumps, ponds, fish ponds, and forests around the airport that attract wild animals. Internal handling is carried out through habitat management, such as installing fences and pruning vegetation, although it is still in the process of being repaired. External handling involves cooperation with BKSDA, PERBAKIN, authorities, and the community to evict, record, and regulate land use so as not to attract wild animals to the airport area.